Shadow wave - Muchamore, Robert (London : Hodder Children's Books, 2014)
"After a tsunami causes massive devastation to a tropical island, its governor sends in the bulldozers to knock down villages, replacing them with luxury hotels. Guarding the governor's family isn't James Adams's idea of the perfect mission, and then retired agent Kyle Blueman comes up with an unofficial and highly dangerous plan of his own. James must choose between loyalty to CHERUB, and loyalty to his oldest friend"--Back cover.
Young Adult
Young Adult
Keywords: Loyalty -- Juvenile fiction; Teenagers -- Juvenile fiction; Loyalty -- Fiction; Teenagers -- Fiction; Loyalty -- Fiction; Teenagers -- Fiction; Spy fiction